Airway Hydration, Apical K(+) Secretion, and the Large-Conductance, Ca(2+)-activated and Voltage-dependent Potassium (BK) Channel - Kis, Adrian (Ann Am Thorac Soc, 2016)
Large-conductance, calcium-activated, and voltage-gated K(+) (BK) channels are expressed in many tissues of the human body, where they play important roles in signaling not only in excitable but also in nonexcitable cells. Because BK channel properties are rendered in part by their association with four β and four γ subunits, their channel function can differ drastically, depending on in which cellular system they are expressed. Recent studies verify the importance of apically expressed BK channels for airway surface liquid homeostasis and therefore of their significant role in mucociliary clearance. Here, we review evidence that inflammatory cytokines, which contribute to airway diseases, can lead to reduced BK activity via a functional down-regulation of the γ regulatory subunit LRRC26. Therefore, manipulation of LRRC26 and pharmacological opening of BK channels represent two novel concepts of targeting epithelial dysfunction in inflammatory airway diseases.